Kajian Evaluasi Pelatihan Program Pengembangan Manajemen - Nuraini, Endah; Hermawan, Aji; Hubeis, Aida Vitayala; Panjaitan, Nurmala K (Jurnal Aplikasi Manajemen, 2016)
Abstract: This study aims to analyze the training evaluation ofMDP; coveringin class training (ICT), and action learning (AL) in affecting individual performance (IP). And also to find which other factors contribute the successfulness action learning of the MDP. The object of this research was a company that implements theMDP in developing its human resources. The research was based on both primary and secondary data. The primary data were gathered from personal interviews; participants, training manager, training provider, facilitators, and participants'supervisor. The secondary data were obtained through the training evaluation sheets, and performance appraisal. Data were analyzed both qualitatively and quantitatively by using SEM-PLS Smart software.Â  The result of this study were (1) ICT was positively and significantly affecting the AL, (2) ICT and AL do not affect the IP simultaneously, (3) Supervisor support showed as a factor in contributing successfulness of the AL. This research can be benefitted as a reference for a company to conduct the MDP training.